Implementing One Health approaches to confront emerging and re-emerging zoonotic disease threats: lessons from PREDICT - Terra R. Kelly; Catherine Machalaba; William B. Karesh; Paulina Zielinska Crook; Kirsten Gilardi; Julius Nziza; Marcela M. Uhart; Erika Alandia Robles; Karen Saylors; Damien O. Joly; Corina Monagin; Prime Mulembakani Mangombo; et al. (BMC, 2020)
Abstract Recurring outbreaks of emerging and re-emerging zoonoses, such as Ebola virus disease, avian influenza, and Nipah virus, serve as a reminder that the health of humans, animals, and the environment are interconnected and that early response to emerging zoonotic pathogens requires a coordinated, interdisciplinary, cross-sectoral approach. As our world becomes increasingly connected, emerging diseases pose a greater threat, requiring coordination at local, regional, and global levels. One Health is a multisectoral, transdisciplinary, and collaborative approach promoted to more effectively address these complex health threats. Despite strong advocacy for One Health, challenges for practical implementation remain. Here we discuss the value of the One Health approach for addressing global health challenges. We also share strategies applied to achieve successful outcomes through the USAID Emerging Pandemic Threats Program PREDICT project, which serve as useful case studies for implementing One Health approaches. Lastly, we explore methods for promoting more formal One Health implementation to capitalize on the added value of shared knowledge and leveraged resources.